2023
DOI: 10.5500/wjt.v13.i1.1
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 in liver transplant patients: Impact and considerations

Abstract: The coronavirus disease 2019 pandemic has significantly impacted liver tran splantation worldwide, leading to major effects on the transplant process, including the pretransplant, perioperative, and post-transplant periods. It is believed that patients with chronic liver disease, especially those with cirrhosis, have a higher risk of complications from coronavirus disease 2019 infection compared to the general population. However, evaluation of coronavirus disease 2019 effects on liver transplant patients has … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 44 publications
0
5
0
Order By: Relevance
“…Medical laboratory professionals directing or performing TDM for tacrolimus (or other TDM drugs) should consider the distribution of measured values observed in their patient population and validate a higher clinical reportable range to meet clinical need, if needed. It is well documented that concurrent administration of Paxlovid (containing ritonavir) and tacrolimus can cause drug-drug interaction with delayed clearance of tacrolimus [ [7] , [8] , [9] , [10] , [11] , [12] , [13] ], though continuous education of healthcare team members is encouraged in order to mitigate concurrent therapies and risk of potential adverse side effects.…”
Section: Conclusion/discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Medical laboratory professionals directing or performing TDM for tacrolimus (or other TDM drugs) should consider the distribution of measured values observed in their patient population and validate a higher clinical reportable range to meet clinical need, if needed. It is well documented that concurrent administration of Paxlovid (containing ritonavir) and tacrolimus can cause drug-drug interaction with delayed clearance of tacrolimus [ [7] , [8] , [9] , [10] , [11] , [12] , [13] ], though continuous education of healthcare team members is encouraged in order to mitigate concurrent therapies and risk of potential adverse side effects.…”
Section: Conclusion/discussionmentioning
confidence: 99%
“…Metabolism of tacrolimus occurs extensively in the liver by cytochrome P450 enzymes (CYP3A4 and CYP3A5) and by P-glycoprotein (PGP) [ 3 , 5 , 6 ]. A drug-drug interaction of Paxlovid (combination of nirmatrelvir/ritonavir) for treatment of SARS-CoV-2 infection (COVID-19) has been widely reported in the literature as ritonavir is known to inhibit CYP3A4 and, to a lesser extent, PGP, which directly impacts tacrolimus metabolism [ [7] , [8] , [9] , [10] , [11] , [12] ]. Co-administration of ritonavir with tacrolimus has been shown to lead to delayed clearance and potential toxic concentrations of tacrolimus in the blood [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, there is limited information about the course of COVID-19 disease in liver transplant patients. 9 In our study, we evaluated the patients who needed hospitalization among COVID-19 positive patients with liver transplant who referred to our hospital, which is the reference pandemic hospital of the region and found 14.3% mortality and 25% ICU rates.…”
Section: Discussionmentioning
confidence: 99%
“… 72 A review of 18 studies, including 1522 COVID-19 infected LT recipients, showed a similar risk of morbidity and mortality as compared to the general population. 73 Rabiee et al noted that change in immunosuppression during Covid infection was not associated with liver injury (mostly dose reduction of mycophenolate and calcineurin inhibitors). 74 Alanine transaminase (ALT) elevation was higher in post-transplant patients with Covid compared to the general population.…”
Section: Methodsmentioning
confidence: 99%